Left Ventricular Function by Pressure-Volume Loop Analysis before and after Percutaneous Repair of Large Atrial Septal Defects - LIM, D. S.; GUTGESELL, HOWARD P.; ROCCHINI, ALBERT P. (Journal of interventional cardiology, 2014)
Aim The intent of the present study was to evaluate changes in ventricular function with percutaneous closure of atrial septal defect (ASD), as it is associated with alterations in ventricular loading and function. Transcatheter occlusion of ASD imparts acute changes in volume loading of the left ventricle (LV) that obscures measurement of ventricular function by load‐dependent indices. To differentiate between changes in ventricular loading and function, load‐independent indices of ventricular function must be utilized. Methods During transcatheter occlusion of ASD, subjects underwent measurement of LV pressure and volume by the conductance catheter method. Load‐dependent indices of ventricular function included: systolic and diastolic pressures, +dP/dtmax, and −dP/dtmax. Load‐independent indices included: elastance and tau, the preload‐independent time constant ofisovolumic relaxation. To obtain elastance, afterload was augmented by phenylephrine bolus pre‐ and post‐device occlusion. Results In total, 29 patients (age 2–79 years) underwent ASD device occlusion (device size 12–38 mm, median 28 mm). Load‐dependent indices were obtained in all, and satisfactory pressure‐volume loops in 11. At baseline, LV end‐diastolic pressure was 5–23 mmHg (13 ± 5 mmHg) and tau was 31 ± 6 ms. Postclosure of the ASD, LV systolic and diastolic pressures rose by 10 ± 11 mmHg and 5 ± 3 mmHg, respectively (P < 0.05), and +dP/dtmax rose from 1,288 ± 313 mmHg/sec to 1,415 ± 465 mmHg/sec (P < 0.05), but −dP/dtmax was unchanged. Elastance significantly improved (9.4 ± 8.3 mmHg/mL vs. 13.0 ± 7.3 mmHg/mL, P < 0.05) and tau was unchanged. Conclusions Transcatheter occlusion of ASD is associated with acute improvement in load‐independent indices of systolic function in this cohort, without significant worsening of the preload‐independent index of diastolic function. (J Interven Cardiol 2014;27:204–211)